New emerging radially aligned carbon nano tubes comprised carbon hollow cylinder as an excellent absorber for electromagnetic environmental pollution. Issue 23 (20th May 2016) - Patel, Ch. Ravi Prakash; Tripathi, Prashant; Singh, Sweta; Singh, Avanish Pratap; Dhawan, S. K.; Kotnala, R. K.; Gupta, Bipin Kumar; Srivastava, O. N.
Abstract : A novel architecture of carbon hollow cylinder made up of radially aligned CNTs as an excellent absorber for electromagnetic radiations. Abstract : Herein, we demonstrated the synthesis of a hollow cylinder with a new architecture of up to several centimeters in diameter and several centimeters long and having ∼100 μm wall thickness. The hollow carbon cylinder was formed by radially aligned CNTs. These CNTs were grown on ferrocene derived Fe nanoparticles deposited throughout the inner wall of the quartz growth tube. This new ingenious carbon architecture was grown by a customized spray pyrolysis method. Furthermore, we also synthesized such carbon hollow cylinders using different precursor concentrations (ferrocene:benzene), different phases and microstructures to evaluate their EMI shielding effectiveness. The structural and microstructural characterizations of these hollow carbon cylinders comprising radially aligned CNTs were examined through various techniques, including XRD, Raman, FTIR, XPS, SEM, TEM, and HRTEM spectroscopy. Furthermore, the magnetic measurements ( M – H ) were performed for such structures to probe the magnetic properties of these carbon hollow cylinders for different concentrations. Furthermore, the EMI shielding through different concentrations of Fe bearing CNTs were explored in detail for tailoring the desired shielding effectiveness value for possible potential applications. Hence, our synthesis method provides a unique architecture for promising next generation building blocks in the form of carbon hollow cylinders made up of radially aligned CNTs over the conventional randomly oriented CNTs. This could be directly used to make it as a co-axial cover for electrical cables to protect them from EMI pollutants.